Integrasi Platform Morfologi Komputasional sarf.one dalam Pembelajaran Sharf: Analisis Capaian Kognitif dan Dinamika Motivasi Mahasiswa - Muhammad Rasyid Ridha; Banna Irfan Ibadillah; Hana Ayu Amalia; Khoirin Nikmah; Enjang Burhanudin Yusuf; Ahmad Mudzakkir Hamzah (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
Arabic morphology (Sharf) is highly complex and opaque, frequently overloading the cognitive capacity of non-native learners. Instruction dominated by conventional rote learning methods is highly susceptible to triggering academic burnout and demotivation. This study employed a mixed-methods, quasi-experimental design to evaluate the effectiveness of the sarf.One computational morphology platform on students' cognitive achievement, learning motivation, and practical experiences. Participants consisted of 32 students from Universitas Muhammadiyah Purwokerto, divided into an experimental group (n=16) and a control group (n=16). Data were analyzed using ANCOVA for cognitive test scores, non-parametric tests for the Self-Determination Theory (SDT)-based motivation questionnaire, and thematic analysis for interview data. The results demonstrated that sarf.One significantly improved students' cognitive achievement (p < 0,001;  = 0,321) by functioning as a visual scaffold that offloads low-level computational burdens. In the affective domain, the intervention yielded a moderate effect size (Hedges' g = 0.534), effectively reducing anxiety and fostering learning autonomy, although statistical significance was hindered by a ceiling effect. In practice, the platform had a positive impact on students' word search speed and accuracy. However, the research implementation also revealed several challenges, such as students' initial cognitive disorientation during interface adaptation. Furthermore, the application's shortcomings, including the lack of contextual meaning features and the discrepancy between its conjugation order and local methods, caused temporary confusion. Qualitative analysis found that students positioned the platform as a complementary assistant, with the ultimate epistemic verification authority (tahqīq) remaining with the lecturer. This study concludes that sarf.one is a transformative pedagogical instrument that urgently requires future improvements, including the addition of translation features and alignment of its interface with the Nusantara tashrīf tradition.